Delivera (Delivery and Assessment Model): the impacts of collaborative teaching on students - Wan Jusoh, Wan Noor Hazlina; Ibrahim, Norlaila; Ahmad, Nor Faezah Ghazi; Nik Hassan, Nik Fakrulhazri (2025)
Collaboration has been shown to enhance student learning and engagement, yet interdisciplinary collaborative teaching remains underexplored. This study investigates how collaborative delivery and assessment in two subjects, i.e., Islamic Consumer Behavior (IMU253) and Fundamentals of Entrepreneurship (ENT300), promote practical knowledge and application among students. Grounded in Synergistic Integration Theory (SIT), this research examines the effects of DELIVERA (Delivery and Assessment Model) collaborative teaching on course learning and application. Mid-semester, an international speaker was invited to deliver insights on the halal market that catered to both subjects’ requirements. At the end of the semester, students were required to submit a video presentation integrating both subjects’ learning outcomes and demonstrating a Shari'ah-compliant business idea. Lecturers assessed the videos using distinct rubrics aligned with each course’s objectives. This quantitative study surveyed 97 students from the March 2024 semester. Findings revealed that 88.6% of students found the international guest speaker beneficial in enhancing their understanding of the halal market, while 92.8% reported they could effectively apply knowledge from both subjects in their assignments. The results highlight the value of collaborative teaching in bridging theoretical learning with real-world application, particularly in Islamic-based and entrepreneurial education. The study recommends broader adoption of collaborative delivery and assessment models in higher education. Future research should explore its impact on students’ long-term memory, critical thinking, and crossdisciplinary problem-solving skills.